National Security and the constitutional right to join military trade unions: Is constitutional amendment an imperative? - Mnisi, Eric Z. (Scientia Militaria - South African Journal of Military Studies, 2017)
The unionisation of the South African Military Forces has tested both lawyers and our legal system. However, there is very little academic commentary on this important subject. In this article, the policy which allowed the unionisation of the South African military, the impact of the policy on national security, and the reasons why the policy failed are discussed. It is argued that, in the South African context, allowing unions in the Defence Force was a big mistake. Such conduct has sacrificed the country’s national security at the altar of soldiers’ right to form and join labour unions. Unions have polarized the military– their propensity to embark on labour actions to threaten to go to embark on labour actions undermine the country’s national security.